AKIBAT HUKUM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 69/PUU-XIII/2015 TERHADAP HAK TANAH PELAKU KAWIN CAMPUR - Jihan Khairunnisa (Justitia et Pax, 2019)
Land ownership for Indonesian citizens the result of mixed marriages without marriage agreement Indonesian citizen can only use the use rights and lease rights to buildings in the ownership of land. This study uses a normative juridical approach. It can be concluded that according to Law No. 5/1960 for Indonesian citizens, mixed marriages may own land with a status other than use rights and lease rights to buildings if there is a marriage agreement before or at the time of marriage. However, after the Constitutional Court ruling number 69 / PUU-XIII / 2015 gave a breath of fresh air for mixed marriages to still be able to receive their constitutional rights by making marriage agreements during the marriage.